Digital leadership in education: a systematic review - Zhu, Rui; Alias, Bity Salwana; Mohd Hamzah, Mohd Izham; Wahab, Jamalullail Abdul (Journal of Education and Learning (EduLearn), 2025)
Digital leadership in educational settings has gained substantial attention in recent years. However, still lacks of a comprehensive understanding of digital leadership. Therefore, this systematic review presents the analysis on three key areas: defining digital leadership, understanding its effect, and analyzing what factors influence digital leadership practice. It aims to reveal the overlooked aspects of digital leadership. Methods involved conducting a systematic review of studies from the Scopus, Web of Science, and EBSCO databases, complemented by searches of citing articles and reference lists. The data gathered were analyzed to identify patterns and gaps in the current literature. As a result, this review suggest that digital leadership should be defined dynamically, taking into account the evolving nature of technology and its integration into education. The effects of digital leadership should focus more on promoting lifelong learning and ensuring digital safety. Future research should delve deeper into the factors influencing digital leadership to provide a more nuanced understanding of its practice. This literature review contributes to a comprehensive understanding of digital leadership by uncovering previously overlooked dimensions and proposing directions for future research.